Linkages between Economic Growth, Poverty and Environmental Quality in Indonesia - Bagus Sumargo; Rahadita Nur Haida (Muhammadiyah University Press, 2020)
The biggest obstacle to sustainable development in Indonesia is due to social-environmental factors. The objective of this study is to identify lever variables in the intended socio-environmental factors through dimensional analysis in sustainable development. By using the path analysis methods and secondary data on economic growth, the number of poor people and an index of environmental quality in Indonesia, 2016, it can be proven that poverty has a direct negative effect on environmental quality. This makes it possible to occur in the rural poverty typology because their needs for life depend on natural resources. Therefore, poverty reduction policies should be prioritized in reducing the number of poor people in rural areas.